2005
DOI: 10.1139/f05-136
|View full text |Cite
|
Sign up to set email alerts
|

Do bears facilitate transfer of salmon resources to aquatic macroinvertebrates?

Abstract: In coastal areas of the Pacific Northwest bears (Ursus spp.) prey heavily on spawning Pacific salmon (Oncorhynchus spp.) and selectively kill energy-rich individuals that are the most recent arrivals on spawning grounds. Pacific salmon eventually die in spawning habitats anyway, albeit with considerably lower energetic content. We investigated whether foraging activities of bears facilitate growth of stream invertebrates by increasing the duration of salmon carcass availability and the nutritional value of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…In the water, they would have been decomposed by scavenging aquatic insects (Minakawa and Gara , Winder et al. ) and bacteria. Dissolved nutrients may leach into hyporheic flows and be acquired by riparian trees (O'Keefe and Edwards ).…”
Section: Discussionmentioning
confidence: 99%
“…In the water, they would have been decomposed by scavenging aquatic insects (Minakawa and Gara , Winder et al. ) and bacteria. Dissolved nutrients may leach into hyporheic flows and be acquired by riparian trees (O'Keefe and Edwards ).…”
Section: Discussionmentioning
confidence: 99%
“…with the highest energy content (large individuals that have spent the fewest number of days on the spawning grounds), which increases the likelihood of transport of those salmon into the riparian zone (Gende et al, ; Hocking & Reimchen, ). Bear‐killed salmon that are left in the river are preferentially colonized by caddisfly larvae compared to senesced carcasses, possibly due to their higher energetic content, improved accessibility, or extended temporal availability (Winder et al, ). This prey selection is also mediated by stream habitat structure, and in complex habitats where preferred salmon are difficult to catch, bears selectively kill older, more senesced individuals (Gende et al, ).…”
Section: Recipient Ecosystem – Consumer Characteristicsmentioning
confidence: 99%
“…This region is also populated by brown bears (Ursus arctos). Long-term surveys of salmon abundance and bear predation in the Wood River System has shown that annual predation rates by bears on sockeye salmon range from 5 to 82% of spawning individuals (Winder et al 2005). We studied riparian habitats of six sites on four streams to investigate the effect of salmon and bears on soil N cycling ( Fig.…”
Section: Site Descriptionmentioning
confidence: 99%